Preparation and characterization of flourescent carbon from calamansi (citrus microcarpa) juice. Jec Reece H. Grabato. - Grabato, Jeb Reece H. (2019.)
Fluorescent carbon is currently of great research interest due to its unique optical properties and biocompatibility. Recent reports used food products as carbon sources due to their availability and non toxicity. In this study, it was shown that fluorescent carbon can be produced through the hydrothermal treatment of pulp-free camalansi (Citrus microcarpa) juicewith urea as passivating agent. The prepared calamansi juice fluorescent carbon (CJFC) exhibit good solubility in the water, but eventually precipitate after several days of storage. SEM micrographs of the CJFC unfortunately only showed the aggregates and there is no visual evidence of the formation of carbon dots. However the succeeding characterization with Fourier transform infrared (FTIR) spectroscopy showed that the CJFC have oxygen-rich groups (OH, COOH, C=O, C-O), and the detected presence of amide groups confirmed the doping of nitrogen from the urea into the fluorescent carbon. Thermogravimetric analysis (TGA) showed that the CJFC start to thermally degrade at 164 °C. The CJFC also possess optical properties. In terms of absorption, aqueous CJFC have a λmax at 333 nm. In terms of emission, the CJFC exhibit excitation-dependent fluorescence probably due to the presence of multiple emitting species. Maximum fluorescence intensity is attained at 561 nm, at an excitation wavelength of 400 nm. The quantum yield (QY) of the CJFC at 330-nm excitation is only 0.680% which is likely due to their aggregation.
Thesis (Undergraduate, Bachelor of Science in Chemistry) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo. 2019.
Keywords: Calamansi; Citrus microcarpa